SYNTHESIS AND CHARACTERIZATION OF A DERIVATIVE CYCLOHEXANONE CHALCONE-TYPE, AS AN INTEGRAL LABORATORY EXPERIENCE - Perla E. Hernández-González; Nancy Romero-Ceronio; Cuauhtémoc Alvarado-Sánchez; Abraham Gómez-Rivera; Carlos E. Lobato-García; Luis J. Romero-Morán (Avances en Ciencias e Ingeniería, 2015)
At present, chemistry teachers are searching new models that allow integrative laboratory experiences, converging interdisciplinary knowledge of the Chemistry field. With this framework of ideas, this work describes the synthesis and characterization of the (2E,6E)-2,6-bis(4-methoxybenzylidene)cyclohexanone compound as axis of knowledge in order to encourage the students to develop their cognitive skills, such as critical thinking and problem solving, and also interpretation and analysis of results. The compound was synthesized by a Claisen-Schmidt condensation reaction, involving an aromatic aldehyde and cyclohexanone. The compound was characterized spectroscopically by NMR, IR and UV-Vis. Melting point and solubility tests were also performed. The chemical structure was confirmed by single crystal X-Ray diffraction. In conclusion, this laboratory experience allows students to get involved with the techniques and procedures commonly used in the organic chemistry laboratory to the synthesis and characterization of organic compounds.